PENGUATAN PENDIDIKAN KARAKTER MELALUI MATA PELAJARAN AQIDAH AKHLAK DI MI RAUDLATUL ULUM PATEMON - Imam, Abdul Karim; Syaeyhotin, Sayyidah (International Conference on Humanity Education and Society (ICHES), 2025)
This study aims to examine the school policy strategy in strengthening character education through Akidah Akhlak learning at MI Raudlatul Ulum Patemon, Jember. The background of this study is based on concerns about the decline in student morality as reflected in various deviant behaviors. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation, and is analyzed using the Miles and Huberman model. The results of the study indicate that MI Raudlatul Ulum Patemon has implemented an integrated school policy in the formation of student character through a religious habituation program, instilling Islamic values ​​in the Akidah Akhlak subject, and teacher role models. Akidah Akhlak learning is a strategic space for internalizing moral values ​​through a thematic and narrative approach. The challenges faced include the absence of standard character evaluation standards and the need to increase teacher capacity. However, parental involvement and a supportive school culture are strengthening factors. This study makes a real contribution to the practice of character education at the elementary school level and recommends the need for replication of similar policies in other educational institutions.